New Directions in Critical Race Theory and Sociology: Racism, White Supremacy, and Resistance. (November 2019) - Christian, Michelle; Seamster, Louise; Ray, Victor
Critical Race Theory (CRT) provides a highly generative perspective for studying racial phenomena in social, legal, and political life, but its integration with sociological theories of race has not been systematic. However, a group of sociologists has begun to show the relevance of CRT for driving empirical inquiry. This special issue (our first of two on the subject) shows the relevance of CRT for sociological theory and empirical research. In this introduction, we identify primary concerns of CRT and show their sociological utility. We argue that CRT better explains the long-standing continuity of racial inequality than theories grounded in "progress paradigm, " as CRT shows how racism and white supremacy are reproduced through multiple changing mechanisms.